2013
DOI: 10.1007/s40265-013-0041-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Assessment of Adherence-Enhancing Interventions in Studies Assessing Medication Adherence Through Electronically Compiled Drug Dosing Histories: A Systematic Literature Review and Meta-Analysis

Abstract: BackgroundNon-adherence to medications is prevalent across all medical conditions that include ambulatory pharmacotherapy and is thus a major barrier to achieving the benefits of otherwise effective medicines.ObjectiveThe objective of this systematic review was to identify and to compare the efficacy of strategies and components thereof that improve implementation of the prescribed drug dosing regimen and maintain long-term persistence, based on quantitative evaluation of effect sizes across the aggregated tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
268
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(301 citation statements)
references
References 108 publications
13
268
1
7
Order By: Relevance
“…64 Furthermore, a recent meta-analysis suggested that electronic-monitoring feedback is potentially an effective approach to enhance patient adherence to medications. 65 In the current review on adherence to BCR-ABL inhibitors for the treatment of CML, only 3 studies measured adherence through an electronic monitor. Nevertheless, the L. Noens et al 442 haematologica | 2014; 99(3)…”
mentioning
confidence: 99%
“…64 Furthermore, a recent meta-analysis suggested that electronic-monitoring feedback is potentially an effective approach to enhance patient adherence to medications. 65 In the current review on adherence to BCR-ABL inhibitors for the treatment of CML, only 3 studies measured adherence through an electronic monitor. Nevertheless, the L. Noens et al 442 haematologica | 2014; 99(3)…”
mentioning
confidence: 99%
“…Particularly good results give those which provide patients with information regarding the drug taking, obtained through objective assessment of adherence [19]. One can hope that the implementation of an electronic patient's record, and electronic prescriptions in Poland, which is to happen within upcoming years, will enable doctors, pharmacists and patients closer insight into details of individual patient's pattern of medication taking.…”
Section: Discussionmentioning
confidence: 99%
“…To note, several founding members of ESPACOMP were involved in the European ABC project (www.abcproject.eu), which revisited the adherence taxonomy and reviewed determinants of medication adherence [1,2]. It also endorsed a meta-analysis on adherence-enhancing interventions through electronically compiled drug dosing histories, published a review on an educational framework for managing and supporting medication adherence in Europe and developed practical consensus-based policy solutions [3][4][5].…”
mentioning
confidence: 99%